The asymptomatic tuberculosis proportion among the elderly population: a systematic review and meta-analysis - Yiqing Zhou; Fei Wang; Songhua Chen; Yu Zhang; Wei Wang; Qian Wu; Dan Luo; Yuxiao Ling; Yang Li; Luyu Wang; Jingru Wei; Bin Chen; et al. (BMC Public Health, 2024)
Abstract Background The elderly population is a high-risk group for tuberculosis, and increasing evidence demonstrates a comparatively high proportion of asymptomatic tuberculosis in this group. This study aimed to determine the proportion of asymptomatic tuberculosis among patients with active tuberculosis through active case finding in the elderly population. Materials and methods We searched for relevant articles published from the establishment of each database to December 31, 2023 in Web of Science, PubMed, VIP database, Chinese National Knowledge Infrastructure, and Wanfang database. The studies’ quality was assessed using the Agency for Healthcare Research and Quality’s criteria. We used the I² statistic and Q test to evaluate heterogeneity across the included studies. We employed subgroup analysis, sensitivity analysis, and meta-regression to pinpoint sources of heterogeneity. Moreover, Begg’s and Egger’s tests were employed to detect any potential publication biases. Results Nine studies involving 364,260 elderly individuals met the criteria for the analysis. In active case finding, the proportion of asymptomatic tuberculosis in the elderly population was 67.7% (95% CI: 54.7–79.5%, I 2 random effects model = 90.197, P < 0.001). The subgroup analysis revealed that the proportion of asymptomatic tuberculosis in high-burden countries was high, at 66.3% (95%CI: 52.5–78.9%, P < 0.001). Studies using multiple screening strategies including chest X-ray showed a higher percentage of asymptomatic patients, at 67.6% (95% CI: 51.1–82.1%, P < 0.001). However, in studies conducted after 2019 and studies with large sample sizes (≥ 15,000), the proportion of asymptomatic tuberculosis decreased (54.3%, 95%CI: 48.6–60.1%; and 62.3%, 95%CI: 45.9–77.4%, respectively). Conclusions The latest results revealed a significantly high percentage of elderly individuals with asymptomatic tuberculosis. This study highlighted the importance of mass screening to identify active tuberculosis cases in this specific group which could help health policymakers develop better strategies to reduce the burden of tuberculosis in the elderly population.